Human epidermal growth factor receptor 2 expression in women with uterine cervix adenocarcinoma from Appalachian Kentucky - Kunos, Charles A.; Fabian, Denise; Piecoro, Dava W.; Napier, Dana; Miller, Rachel W.; Ueland, Frederick R. (Frontiers in Oncology, 2023)
High-risk human epidermal growth factor receptor 2 (HER2)-positive adenocarcinomas associate with early recurrence and death, prompting consideration of novel radiotherapeutic options like a trastuzumab-linked thorium-227 alpha-particle emitting radionuclide. We conducted a retrospective pilot biomarker study of uterine cervix cancers among patients in Appalachian Kentucky, to characterize an exploitable triage biomarker like HER2 expression before starting a prospective phase 0 trial. Most (60%) adenocarcinomas showed HER2 cell-surface overexpression, whereas squamous cell carcinomas (4%) did not do so. Further validation tests of HER2 expression as a triage biomarker for radiopharmaceutical selection are warranted.